Three-Dimensional Nonlinear Dynamic Analysis of Base Isolated Cylindrical Steel Tank - Abdellali Saria; Mohamed Djermane; Nasser Dine Hadj-Djelloul (Salehan Institute of Higher Education, 2022)
Failure of a tank during an earthquake can result in significant financial, human, and environmental losses. Thus, their lack of resiliency against strong earthquakes may result in refinery disruption. This has the potential to have a considerable impact on any economic system. As a result, more research into the seismic performance of tank structures is required to attain the highest possible level of resistance against strong earthquakes. In this paper, we aim to look into the installation of seismic isolation systems in cylindrical steel storage tanks. A nonlinear 3D finite element model is developed with ANSYS software. Moreover, tank wall material nonlinearity, fluid-structure-interaction, and sloshing components are considered. The bilinear hysteretic LRB is used for modal and time-history analysis. In this work, three tanks with varying aspect ratios are studied: